Proposal of a Dedicated Telemetry Device for Real-Time and Remote Measurements - Pissolato Filho, Jose; Zanotto, Andre C.; Costa, Eduardo C. M.; Kurokawa, Sergio [UNESP]; IEEE (Ieee, 2011)
This work aims to demonstrate an application of telemetry for monitoring process variables. The authors developed the prototype of a dedicated device capable of multiplexing, encoding and transmitting real-time data signals via amplitude-shift keying modulation to remotely located device(s). The prototype development is described in details, enabling the reproduction of the proposed telemetry system for a three-phase motor as well as for other devices. Furthermore, the proposed device has an easy implementation by using of accessible components and low cost, also presenting a tutorial and educational purpose.
Keywords: Telemetry of process variables; dedicated systems; switching power supplies; multiplexing and encoding of data signals; RF circuits; amplitude-shift keying modulation